(untitled) (Revista de Estudos da Linguagem, 2004)
In Brazilian Portuguese reduction occurs in some pronouns, for instance, cê (from você); el and ez (from the pronouns ele and eles);num (from não) and others that have been analyzed as becoming clitics (VITRAL & RAMOS, 2002). In order to prove this hypothesis,we collected a corpus with almost 500 utterances containing the reduced forms above. The reduced forms were acoustically analyzed considering the intensity and duration parameters and then compared with those parameters of real clitics. This paper presents the research results and the conclusions we have achieved in this work.